2021
DOI: 10.3390/ijerph18105476
|View full text |Cite
|
Sign up to set email alerts
|

E-Cigarette Use in Young Adult Never Cigarette Smokers with Disabilities: Results from the Behavioral Risk Factor Surveillance System Survey

Abstract: Young adult never cigarette smokers with disabilities may be at particular risk for adopting e-cigarettes, but little attention has been paid to these people. This study examines the associations between different types of disability and e-cigarette use in this population. Young adult never-smokers from the 2016–2017 Behavioral Risk Factor Surveillance System (BRFSS) survey who were either never or current e-cigarette users (n = 79,177) were selected for the analysis. The Least Absolute Shrinkage and Selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Fifth, while tobacco use has been linked with mental health conditions such as anxiety and depression [13], it was beyond the scope of our study to investigate the relationship PLOS GLOBAL PUBLIC HEALTH between disability, mental health, and tobacco use. Lastly, while some recent studies have demonstrated disparities in e-cigarette use between adults with disabilities and those without [56][57][58], little or no DHS data were available on e-cigarettes or other non-combustible nicotine and tobacco products (e.g., heated tobacco products, nicotine pouches, etc. ); this is an area for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, while tobacco use has been linked with mental health conditions such as anxiety and depression [13], it was beyond the scope of our study to investigate the relationship PLOS GLOBAL PUBLIC HEALTH between disability, mental health, and tobacco use. Lastly, while some recent studies have demonstrated disparities in e-cigarette use between adults with disabilities and those without [56][57][58], little or no DHS data were available on e-cigarettes or other non-combustible nicotine and tobacco products (e.g., heated tobacco products, nicotine pouches, etc. ); this is an area for future work.…”
Section: Discussionmentioning
confidence: 99%